CORRELATION OF PSYCHOLOGICAL MALADJUSTMENT, SOCIAL SUPPORT AND PSYCHOSOMATIC HEALTH IN FRESHMAN AMONG COLLEGE STUDENTS - Kong, Lingming; Zhu, Xiaoli; Zhang, Liyi (International Journal of Research -GRANTHAALAYAH, 2022)
To investigate the relationship between psychosomatic health and psychological maladjustment, social support in freshman. By random cluster sampling, 2790 freshmen garrisoned on islands (study group) and 2790 sophomore and junior college students as control group were recruited in Changzhou and administered by Chinese Psychosomatic Health Scale (CPHS), Maladjustment Self-Assessment Scale (MSAS) and Chinese Social Support Scale (CSSS). The results were analyzed with t test analysis, Pearson correlation and stepwise regression analysis by SPSS statistic 17.0. Compared with the controls, freshmen had higher scores of psychological disorder(anxiety depression, psychoticism) and of somatic disorder(respiratory apparatus, cardiovascular system, alimentary system, skeletal and musculature, integument, regenerative and endocrine, nervous system) except the factor of eye and ear; all factors of CPHS had positive correlation with most factors of MSAS, CSSS; regression analysis showed that behavioral problem, interpersonal relationship, environmental adaptation, subjective support, support degree of use entered into the regression equation. In conclusion, the psychosomatic health in freshman among college students is generally worse than those of the controls. Behavioral problem, interpersonal relationship, environmental adaptation, subjective support, support degree of use are associative factors predictive factors.